SOME ISSUES THAT ARISE WHEN DEFINING PREDICATE CRIMES FOR CRIMES RELATED TO MONEY LAUNDERING - Khazratali Qudratillaev (Scholar Express Journals, 2023)
This article describes the main crimes that lead to the commission of crimes related to the legalization of proceeds from criminal activity, that is, the term predicate crimes. The article analyzes the requirements set for predicate crimes in the FATF, the main organization in this field, and the Conventions regulating this field. In addition, the article examines the experience of foreign countries, their level of implementation of FATF requirements on predicate crimes, problems arising during implementation. At the end of the article, proposals for the Criminal Code of the Republic of Uzbekistan were developed and the term "predicate crimes" was defined.
Keywords: Predicate crimes; FATF; legalization; Convention